BUDIDAYA LELE DUMBO (Clarias gariepinus DENGAN VOLUME PENGGANTIAN AIR BERBEDA AFRICAN CATFISH (Clarias gariepinus) CULTURE WITH DIFFERENT WATER EXCHANGE VOLUME - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2000)
African catfish were cultured in fibreglass containers in two periods, two months and three months culture period consecutively without draining. Water in the container were replaced daily at rate of 0, 5, 10, 20 and 40 percent volume. Objectives of this research were to know the growth of fish and water quality during the two periods. Results of this experiment indicated that 1). fish production were not affected by water replacement. 2). The more the water being replaced the better the water quality, however based on fish production point of view replacement at of 5 % volume/day was the most feasible technique.